MEMANFAATKAN UU PATEN NO. 14 TAHUN 2001 UNTUK PENGEMBANGAN PATEN NASIONAL - Maulana, Insan Budi (E-Journal Widya Yustisia, 2005)
Although Indonesia already has a Patent Law, namely Law No. 6 of 1989, which came into effect on 1 August 1991 and then amended under Law No. 13 of 1997 on Patents and most recently under Law No. 14 of 2001 on Patents, which came into effect on 1 August 2001, Indonesia has not been able to effectively utilize such law since domestic patent applications received at the patent office is still around 5% of the entire patent applications numbering 23.000 inventions between 2000 and 2005. Therefore it is necessary to conduct effective promulgation to researchers and national business people, allocate adequate funds and prioritize patents to be developed